2004
DOI: 10.1554/03-334
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Pattern of Africanization in a Feral Honeybee Population From Texas Inferred From Mitochondrial Dna

Abstract: Abstract. The invasion of Africanized honeybees (Apis mellifera L.) in the Americas provides a window of opportunity to study the dynamics of secondary contact of subspecies of bees that evolved in allopatry in ecologically distinctive habitats of the Old World. We report here the results of an 11-year mitochondrial DNA survey of a feral honeybee population from southern United States (Texas). The mitochondrial haplotype (mitotype) frequencies changed radically during the 11-year study period. Prior to immigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
48
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(50 citation statements)
references
References 63 publications
2
48
0
Order By: Relevance
“…In the subtropical-swarm traps (91 samples) (see Pinto et al 2004 for details on tested for each locus and population sample using the Hardysampling procedure).…”
Section: Hallmentioning
confidence: 99%
See 4 more Smart Citations
“…In the subtropical-swarm traps (91 samples) (see Pinto et al 2004 for details on tested for each locus and population sample using the Hardysampling procedure).…”
Section: Hallmentioning
confidence: 99%
“…Surveys of allozymes (Del Lama et al 1988;Lobo et al 1989 . m. et al 1991b;Diniz et al 2003), restriction fragment length polymorphisms (Hall 1990; McMichael and scutellata mitotype (Pinto et al 2004). In spite of the initial trend, the authors found a substantial contribuHall 1996; Hall and McMichael 2001), randomly amplified polymorphic DNA (Suazo et al 1998), and tion of non-A.…”
mentioning
confidence: 99%
See 3 more Smart Citations